Most common cause of cardiomegaly without significant murmur in pediatric age group at tertiary care hospital, Hyderabad, India: a prospective observational study - Mohan Chekkali, Chandra; Kotha, Rakesh; Singh, Himabindu; Bapanpalli, Narahari; Anjum, Sadiqua; ., Alimelu; Jadhao, Arjun (International Journal of Contemporary Pediatrics, 2019)
Background: Following the invention of monaural stethoscope by Laennec and X ray by Roentgen in 18th century there was spectacular advancements in cardiology. The myocardium can be affected by various disease process unrelated to abnormal pressure or volume loads. These processes may be inflammatory, metabolic, infiltrative, ischemic or primary with significant overlap. These diseases usually present as cardiomegaly. In pediatric age group cardiac diseases will present early, sometimes without any signs and symptoms like sudden death due to less cardiac reserve. Few cases of sudden death also showed huge cardiomegaly in postmortem X rays. authors want to carry out this study to find out most common cause of cardiomegaly with silent chest as authors usually miss the diagnosis and these cases may present as sudden death without giving much time to intervene. The aim of the study is to know the most common cause of cardiomegaly without significant murmur in pediatric age group above one year. Methods: Prospective observational study done at a tertiary care hospital Hyderabad over a period of one year from January 2018 to January2019. Results: Most common cause of cardiomegaly without significant murmur was cardiac beriberi. It is mostly prevalent in rural areas of Telangana, mostly occurring in breastfed babies and below six years. All cases were recovered after proper treatment. Fortunately, it is associated with nil mortality, if timely treatment was initiated. Conclusions: Cardiac beriberi which is easily preventable and if treated in proper time it will associated with nil mortality. As it was occurring commonly breastfed babies supplementation of Thiamine to mothers was very useful as a preventive strategy.